2020
DOI: 10.1021/acs.langmuir.0c01102
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of Simultaneous Extraction of Silver and Gold Nanoparticles across Aqueous–Organic Interfaces by Surface Active Iron Oxide Nanoparticles

Abstract: Surface active iron oxide nanoparticles (NPs) were used for the simultaneous extraction of water soluble Ag and Au NPs across an aqueous− organic interface from aqueous bulk. The surface activity of iron oxide NPs was achieved by using cationic Gemini surfactants of different architectures during the in situ synthesis of iron oxide NPs in hydrothermal synthesis. Aqueous bulk solubility of Ag and Au NPs was achieved by stabilizing them with conventional surfactants of different polarities such as SDS, CTAB, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…The NP–NP interactions can also be screened by using interfering magnetic NPs, which possess the ability to interact with either/both Au and Ag NPs simultaneously . In order to depict this, we selected the titration of Figure c where maximum Au–Ag NPs interactions are observed (Figure f).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The NP–NP interactions can also be screened by using interfering magnetic NPs, which possess the ability to interact with either/both Au and Ag NPs simultaneously . In order to depict this, we selected the titration of Figure c where maximum Au–Ag NPs interactions are observed (Figure f).…”
Section: Resultsmentioning
confidence: 83%
“…Here, we show the effect of the monomeric to polymeric Gemini surfactant head group on NP–NP electrostatic interactions by comparing the UV–visible titrations of SDLC-stabilized Ag NPs (titrand) with 12-0-12 (monomeric)-, 12-6-12 (dimeric)-, and TriCAT (trimeric)-stabilized Au NPs (titrant) in Figure . Figure a shows a small change in the absorbance of Ag NPs upon titrating with 12-0-12-stabilized Au NPs along with a little change in the color of the sample (inset sample photos).…”
Section: Resultsmentioning
confidence: 99%
“…Iron oxide NPs were synthesized by following the hydrothermal synthesis reported earlier. Typically, a total of 20 mL of the reaction mixture containing 4 mM of FeCl 3 and 4 mM of Fe 2 SO 4 in a 1:1 mol ratio were placed in a Teflon container along with 250 mg of a stabilizing agent (SDS, 12-2-12, or DPS). The addition of 30% ammonium hydroxide initiated base catalyzed hydrolysis.…”
Section: Methodsmentioning
confidence: 99%
“…Surface active magnetic nanoparticles (NPs) prefer to adsorb at aqueous–air, aqueous–organic, or aqueous–solid interfaces. , This ability promotes extraordinary interfacial applications of magnetic NPs without incorporating aqueous bulk. The selective extraction of an analyte from the aqueous bulk by using magnetic NPs is one of the most promising applications that can be applied for the extraction of proteins from complex biological media and pollutants from fresh water resources .…”
Section: Introductionmentioning
confidence: 99%
“…Bakshi et al [64] reports an interesting method for the removal of Au and Ag nanoparticles from water solution through the addition of magnetic iron oxide nanoparticles (average size~20 nm) which have been synthesized in the presence of a gemini surfactant, namely a long-chained amino ion through a solvothermal synthesis. It was observed that these surfactants can form an amphiphilic structure which can serve to draw metallic nanoparticles of different surface polarities away from free media to an organic/water interface, enabling removal with a magnet.…”
Section: Metal Ferrite Magnetic Nanoparticlesmentioning
confidence: 99%